The Trend in Using Online Meeting Applications for Learning During the Period of Pandemic COVID-19: A Literature Review - Hendri Pratama; Mohamed Nor Azhari Azman; Gulzhaina K. Kassymova; Shakizat S. Duisenbayeva (Journal of Innovation in Educational and Cultural Research, 2020)
The pandemic COVID-19 has given a very significant impact on the lives of the world community, especially in the field of education. The existence of remote learning is an alternative for the community to reduce the impact of outbreaks. This alternative changes the direction of physical learning into online and virtual learning. The use of online meeting applications is an option that provides many conveniences for students and teachers to achieve learning goals without being in class. Various types of applications can be used by the needs and interests of the people. This study is carried out to examine the trend in using online meeting applications to learn during the outbreak period. This study was conducted using qualitative methods through descriptive analysis of the results of observations and documentation. This scenario shows the increment of the usage of these applications in the teaching and learning process (PP). The use of this application is very helpful in the teaching and learning process between teachers and students. Overall, there is an increasing trend and give the effect towards usage of online meeting applications in solving learning problems in the future.